Pembongkaran dan Pemindahan Mayat Perspektif Mazhab Al-Syafi’i dan Mazhab Hanbali: Studi Perbandingan - Putri, Angelina Atika; Sabir, Muhammad; Alimuddin (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
The dismantling and removal of the skeleton raises new questions about its capabilities. The main problem in this study is how the law of Transfer of Corpses with a comparative approach between the views of the Al-Shafi'i and Hanbali Schools. The purpose of this study was to find out the Law of Transfer of Corpses with a comparative approach between the views of the Al-Shafi'i and Hanbali Schools. This research uses a type of qualitative research (Library Research), with primary and secondary data sources where primary data uses literature such as books, journals of scientific papers in the form of theses, theses, data information and websites and uses a comparative normative approach in analyzing data and using content analysis and conclusion making and using deductive conclusion drawing methods. The results showed that Imam Shafi'iyah argued that moving a dead body before burial from the place of death to another place was haram, even though the smell of the corpse was guaranteed not to change, unless they used to bury the bodies outside their area. Imam Hambali argued that even moving a body from the place of death to a distant place was okay on the condition that the transfer was done for the right purpose.